Mental Health in School-Aged Children Prenatally Exposed to Alcohol and Other Substances - Lisbeth Beate Sandtorv; Mari Hysing; Malin Rognlid; Sondre Aasen Nilsen; Irene Bircow Elgen (SAGE Publishing, 2017)
Prenatal exposure to substances can possibly influence a child's neurodevelopment and may impact on subsequent mental health. We investigated the mental health status of school-aged children referred to a pediatric hospital with a history of prenatal exposure to alcohol or other substances. Mental health was assessed using the Strengths and Difficulties Questionnaire and compared with a reference group. A total of 105 of 128 (82%) eligible children prenatally exposed to substances participated in the study, with 48 children exposed to alcohol and 57 to other substances. Strengths and Difficulties Questionnaire subscale mean scores, total difficulties scores, and total impact scores were statistically significantly higher in the group of exposed children, compared with the reference group. In this hospital-based population of school-aged children prenatally exposed to alcohol or other substances, the exposed group had an increased risk of mental health problems, compared with the reference group.